MANAJEMEN MUTU BERBASIS NILAI ISLAMI DALAM MENINGKATKAN PROFESIONALISME GURU DI MADRASAH TSANAWIYAH KEMUNING PACITAN - Eka Nur Marlia; Fathi Nur Jannah; Zettira Shifa Salsabila; Febri Marnisa Harahap (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of quality management based on Islamic values in improving teacher professionalism at MTs Kemuning Pacitan. This research employs a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation. The subjects of this study were teachers and the head of the madrasah, while the object focused on the implementation of quality management and its impact on teacher professionalism. The findings reveal that quality management has been implemented through the main functions of educational management, namely planning, organizing, implementation, and evaluation. Islamic values such as sincerity (ikhlas), trustworthiness (amanah), discipline, and responsibility are integrated through religious activities and moral development programs. The head of the madrasah plays a crucial role in enhancing teacher professionalism through teacher selection, training, supervision, and competency development programs such as workshops and professional forums. The implementation of this approach has a positive impact on increasing teachers’ awareness, responsibility, and commitment in carrying out their duties. However, several challenges remain, including limited facilities and infrastructure, differences in teachers’ educational backgrounds, and the uneven integration of Islamic values into the learning process.